Pendekatan Object-Oriented Analysis and Design (OOAD) dalam aplikasi pemesanan pakaian Dennis Collection - Natsir, Fauzan; Kurniawan, Indra (Universitas Merdeka Malang, 2025)
Dennis Collection is a clothing company located in East Jakarta that offers a variety of clothing items such as t-shirts, shirts, jackets, dresses, and sleepwear. The company is competitive and able to provide satisfying service to its customers. However, to this day, all sales transaction data and information processing are still recorded manually in notebooks. This research aims to facilitate the sales process, inventory management, and transaction reporting through a web-based clothing ordering system. In the system development stages, the Object-Oriented Analysis and Design (OOAD) method was used to analyze and design the system using an object-oriented approach. Based on the results of the User Acceptance Testing (UAT), the developed clothing ordering system is considered feasible to be used as an application that supports the management of clothing order data, with an average user score of 97.5%. This study is expected to help provide a solution for Dennis Collection in optimizing the management of sales data and inventory more effectively and cost-efficiently.